New Health Sciences Descriptors to classify and retrieve information on equity - Ana Cristina Espíndola Campos; Arthur Treuherz; Renato Toshiyuki Murasaki; Diego Gonzalez; Oscar J Mújica (Pan American Health Organization, 2021)
The Health Sciences Descriptors (DeCS) vocabulary establishes a unique and common language that allows the organization and facilitates the search and retrieval of technical and scientific literature on health available in the information sources of the Virtual Health Library. The DeCS, created by the Latin American and Caribbean Center on Health Sciences Information (BIREME), a specialized center of the Pan American Health Organization/World Health Organization (PAHO/WHO), is the translation and extension of the Medical Subject Headings (MeSH) vocabulary, maintained by the United States National Library of Medicine. BIREME, in coordination with experts from Latin America and the Caribbean, has included in the DeCS the topics of equity, gender, ethnicity and human rights-cross-cutting themes in the programmatic framework of PAHO/WHO technical cooperation-to ensure better retrieval and use of scientific information and evidence related to these topics. The objective of this article is to describe the methodology used during the terminology review of the DeCS and to report the results obtained and the impacts of the terminology expansion in the field of equity, which included the inclusion of 35 new descriptors.